Smart Heart, Bright Future: Edukasi Gaya Hidup Sehat untuk Mencegah Penyakit Jantung Koroner Sejak Dini Bagi Siswa SMK Pusdikpal Cimah - Budi Rustandi; Theophylia Melisa Manumara; Tiara Nurhibah; Dede Risma Amalia; Mia Amelia; Salsa Putri Nabil; Bunga Riase Amalia; Riki Muhammad Ramdani; Mila Saidah; Zephania Sheryl Hakeema; Naesyha Nirmalasari; Tiara Andita Septiani; Putri Mutiara Nisa (Jurnal Medika: Medika, 2026)
Coronary Heart Disease (CHD) is a serious medical condition that requires understanding and prompt action to prevent fatal complications. Adequate knowledge about CHD is crucial, especially for SMK Pusdikpal students as part of efforts to increase health awareness among the younger generation. This activity aims to enhance SMK Pusdikpal students' knowledge regarding CHD through scientific journal-based health education. This method uses a quasi-experimental approach with a pretest-posttest design involving 28 students. The intervention consists of learning delivered through summaries and discussions of scientific journals related to CHD presented in PowerPoint format. The results show a significant increase in students' knowledge scores based on the comparison of pretest and posttest questionnaires as well as participation in interactive discussions during material delivery (p < 0.05). This assessment includes baseline initial knowledge (pretest), understanding during the session through interaction, and final evaluation (posttest) to measure the effectiveness of the intervention comprehensively. In conclusion, scientific journal-based health education is effective in improving SMK Pusdikpal students' knowledge about CHD, and is therefore expected to increase awareness and preparedness in facing coronary heart disease risks.